2017
DOI: 10.3311/ppme.9283
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Finite Element Analysis of Turning Processes

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Researchers have used finite element method to predict the effect of machining parameters (cutting speed, depth of cut, tool geometry and feed rate) on the cutting forces, chip formation, temperature, stress and pressure distributions [41,42]. The results obtained from FEA have shown to be comparable with experimental results [43,44]. In this study, DEFORM 3D ® v11.0 software has been used to study orthogonal turning of Ti-6Al-4V alloy shown in Figure 1a.…”
Section: Finite Element Simulation On Deform 3dmentioning
confidence: 99%
“…Researchers have used finite element method to predict the effect of machining parameters (cutting speed, depth of cut, tool geometry and feed rate) on the cutting forces, chip formation, temperature, stress and pressure distributions [41,42]. The results obtained from FEA have shown to be comparable with experimental results [43,44]. In this study, DEFORM 3D ® v11.0 software has been used to study orthogonal turning of Ti-6Al-4V alloy shown in Figure 1a.…”
Section: Finite Element Simulation On Deform 3dmentioning
confidence: 99%
“…The FE model consists of a 1000 × 300 µm 2D workpiece [21][22][23]. The tool is considered perfectly rigid and presents a rounded tip fillet whose radius is 0.75 µm.…”
Section: Abaqus Fe Modelmentioning
confidence: 99%
“…2 (e.g., grooved shaft). Cutting processing simulations are based on the energy generated in contact tool -metal chips, etc., cutting forces and cutting temperatures (contact tool -metal chips and on the very tool) [10,13]. For the purpose of a more complete analysis of numerical studies for simulations in the Third Wave AdvantEdge program, two mathematical models related to thermo-mechanical characteristics of the workpiece were used [14,15].…”
Section: Simulation Of Continuous and Discontinuous Turning Processmentioning
confidence: 99%